Perancangan Dan Pembuatan Sistem Informasi Penilaian Pada SMA Negeri 1 Munthe - Edy Budi Harjono Sibarani (PT. ALHAFI BERKAH INDONESIA, 2023)
The design of web-based assessment system that is expected to provide convenience in how to access it, to help communication between teachers and parents so that students can more easily and also teachers can process value beyond working hours of work. The method used is descriptive method, data collection method (observation, interview, literature study, documentation study). Data analysis techniques that use the Unified Modeling Language (UML) technique. As well as system design techniques using HTML and PHP programming languages, Adobe Dreamweaver CS6 as the creation of interface systems and using MySQL to design the Database. Based on the results of these studies, the authors built a Web-based assessment information system as a Value Processing System. The existence of a web-based system will make it easier for work to be done anywhere and anytime. Because this information system is a web-based application, then this information system can be published through internet network. Implementing the latest information technology, especially data security technology that can improve system security.